Pengaruh Firm Size, Growth Opportunity Dan Likuiditas Terhadap Pengambilan Keputusan Hedging (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Via Ainun Nur Habibah; Abdul Kodir Djaelani; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This study aims to determine the effect of Firm Size, Growth Opportunity, and Liquidity on Hedging decisions in Manufacturing Companies listed on the Indonesia Stock Exchange from 2016 to 2018 . This type of research is a quantitative study and the data used is secondary data in the form of company financial reports. The population of companies used are manufacturing companies listed on the Indonesia Stock Exchange that conduct foreign exchange transactions and hedging . The research sample was obtained by using purposive sampling method , from 38 companies, There are 13 companies that match the criteria that have been determined as samples with a research period of three years. The data analysis technique used in this study is the Logistic Regression method because the dependent variable is dichotomous. Based on the results of the study, it shows that the Firm Size variable proxied by LnTA has no and insignificant effect on the hedging decision , the Growth Opportunity variable which is proxied by Growth has an effect and is significant on hedging decision making , and the Liquidity variable proxied by CR has no effect and is not significant hedging decisions . Keywords: Firm Size (LnTA), Growth Opportunity (Growth), Liquidity (CR), Hedging.